On-line Copper Removal for Se Determination by Hydride Generation-Inductively Coupled Plasma Optical Emission Spectrometry - Kaplan, Marcos Manuel (2006)
Selenium determination in samples with a high copper content by hydride generation-inductively coupled plasma optical emission spectrometry (HG-ICP-OES) after online copper removal and selenium (VI) reduction is described. An activated carbon minicolumn was used for the retention of copper and its subsequent separation of Se. Se(VI) was then online reduced by heating into a PTFE coiled reactor with 12 M HCl. The analyte was introduced into a water stream containing sodium tetrahydroborate (NaBH4) in order to generate selenium hydride (H2Se). The detection limit (DL) obtained was 0.8 μg L-1, and the precision, expressed by the relative standard deviation (RSD), was 2.5% (n = 10; 10 μg L-1 selenium level). The current method was applied to the Se determination in two copper reference materials, MBH-39DK 3601 (with a Se content of 90 mg kg-1) and MBH-39 DK 3604 (with a Se content of 15 mg kg-1).